Automating computations for electric circuit analysis - Karpa, Mykhailo; Betsyl, Vitalii (Видавництво Львівської політехніки, 2024)
The article considers the application of the theory of the complex variable function employing the LabVIEW graphical programming environment for automating the calculation of electric circuits. The software products have been created to implement the method of constructing the matrix of the system of linear algebraic equations by inspection for both the mesh current method and nodal potential method in electric circuits of direct and alternating current and voltage using a graphical programming environment, except for circuits with dependent sources. All developed programs can be converted into .exe files, with subsequent utilization on computers that do not have a program environment installed. These software solutions can help lecturers quickly generate solutions for new assignments, saving valuable time. Students can utilize these software products for self-control, further reducing their workload.
Keywords: Complex numbers; Nodal analysis; Mesh analysis; LabVIEW